Being, person, animal: The ontological axiology of Antonio Rosmini - Caro Plaza, Ramón (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
The present work reconstructs the axiological theory of Antonio Rosmini, based on his ontological work Theosophy and in confrontation with the contemporary interpretation of the author. From the parameters and challenges of modernity, the philosopher justifies an objective and metaphysical conception of knowledge during his first writings on epistemology. This conclusion leads to a conception of good as an order of reality, thus recovering the nucleus of the classical paradigm, which discovers in being itself the criterion of goodness. Here we will pay attention to that order not from an intrinsic approach to each entity, but from a comparative one of the different entities. In this way, we will describe the hierarchy that is contemplated in the cosmos, where the value of the animal subject and the absolute dignity of the human person will emerge
Keywords: Rosmini; Theosophy; Ethics; axiology; good; value; dignity; person; animal